MODEL KOMPETISI MODA ANGKUTAN BARANG ANTARA KERETA API DAN TRUK DENGAN TEKNIK STATED PREFERENCE - Hermawan, Wawan
On freight transportation there are competition between rail and trucks in which an uneven market segment share. Demand of rail transport still very low compare to the trucks. This phenomenon indicates the importance of understanding the freight shippers behavior by making models. On This research the modelling is directed toward disaggregat approach with a stated preference technique and utilizing binomial logit models, aims at: Identifying for a few factors affecting the mode choice for certain commodities that an originated from Bandung to Jakarta. Developing models which can explain the choice behavior of freight mode tansportation. Measuring of the sensitivity of the shippers responses towards the changes of travel and service attributes considered in the model. The model formulation is determined according to market segment shares which comprises Container-Export (C-E), Non Container-Export (NC-E), Non Container - Domestic (NC-D) and OVERALL segment market. Generally the modelling result is relatively good as indicated by the rho-squared value of 0.465. The conclusion of modelling results regarding the freight shipping are: The safety become main factor for export purpose, in C-E as well as in NC-E, followed by the time factor, while the cost factor for export purposes does not significantly influence the mode selection. In domestic market (NC-D), safety, time and cost factors are all considered in freight shipping. Access to terminals is a factor considered in non-container shipping, in NC-E as well as in NC-D. The result of models applied through a scenario of toll road construction from Padalarang to Cikampek. By constructing this toll road, the probability of truck users will increase by 30%. The result of research is hoped to be used as a tool for determining strategic policies of freight transportation developement.